Bt Cotton and farmer suicides in India: Reviewing the evidence - Gruère, Guillaume P.; Mehta-Bhatt, Purvi; Sengupta, Debdatta (International Food Policy Research Institute, 2008)
Suicides in general, including farmers' suicides, are a sad and complex phenomenon. Hence, their underlying causes need to be addressed within an equally complex societal framework. Here, we provide a specific case study on the potential link between technological choices and farmer suicides in India. Although officially recognized for having increased production and farmers' income, Bt cotton, genetically-modified, insect-resistant cotton, remains highly controversial in India. Among other allegations, it is accused of being the main reason for a resurgence of farmer suicides in India. In this paper, we provide a comprehensive review of evidence on Bt cotton and farmer suicides, taking into account information from published official and unofficial reports, peer-reviewed journal articles, published studies, media news clips, magazine articles, and radio broadcasts from India, Asia, and international sources from 2002 to 2007. The review is used to evaluate a set of hypotheses on whether or not there has been a resurgence of farmer suicides, and the potential relationship suicide may have with the use of Bt cotton. We first show that there is no evidence in available data of a resurgence" of farmer suicides in India in the last five years. Second, we find that Bt cotton technology has been very effective overall in India. However, the context in which Bt cotton was introduced has generated disappointing results in some particular districts and seasons. Third, our analysis clearly shows that Bt cotton is neither a necessary nor a sufficient condition for the occurrence of farmer suicides. In contrast, many other factors have likely played a prominent role. Nevertheless, in specific regions and years, where Bt cotton may have indirectly contributed to farmer indebtedness, leading to suicides, its failure was mainly the result of the context or environment in which it was planted. We close the paper by proposing a conceptual framework for empirical applications linking the different agricultural and institutional factors that could have contributed to farmer suicides in recent years in certain districts of Central and Southern India."